(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Currently, increasing the corrosion resistance of products made from structural steels, developing resource-saving and controlled technologies, intensifying processes and improving the quality of products are the most important tasks facing the modern engineering industry.